Case Report: Enhanced Diazepam Elimination With the Molecular Adsorbents Recirculating System (MARS) in Severe Autointoxication: A Survival Case Report - Dobisova, Anna; Vavrinec, Peter; Vavrincova-Yaghi, Diana; Gebhardtova, Andrea; Henning, Robert H.; Yaghi, Aktham (Frontiers in Medicine, 2021)
Objective: Due to the extensive use of diazepam worldwide, self-induced intoxication is very common, yet rarely fatal. Nevertheless, the management of intoxication caused by extremely high doses of diazepam is not known, as well as the effectiveness of flumazenil, a specific benzodiazepine (BDZ) antagonist. Here we present the first report on the enhanced elimination (clearance) of diazepam using the Molecular Adsorbents Recirculating System (MARS) following autointoxication with an extremely high dose as part of a suicide attempt. Case: A 44-year-old male patient was admitted to the ICU because of impaired consciousness following the ingestion of 20 g of diazepam. Blood and urine samples revealed high benzodiazepine levels. Repeated doses of flumazenil were without effect on consciousness. Following deterioration of the patient's clinical condition, including unconsciousness, hypoventilation, and decreased SpO2 (88%), the patient was intubated and mechanically ventilated. On the fourth day after admission, the patient was unresponsive, with no attempt to breath spontaneously. The plasma level of benzodiazepines was 1,772 μg/l. The elimination of benzodiazepines by MARS was attempted, continuing for 5 days, with one session per day. Five sessions of MARS effectively enhanced benzodiazepine elimination. After the first MARS treatment, the plasma level of benzodiazepines dropped from 1,772 to 780 μg/l. After the final MARS treatment on the eighth day, the patient was weaned from mechanical ventilation and extubated. Two days later, the patient was discharged to the internal medicine department and subsequently to the psychiatry department. Conclusions: To the best of our knowledge, this is the first case reporting successful treatment of diazepam intoxication using MARS. In severe cases of diazepam intoxication, with prolonged unconsciousness and the necessity of mechanical ventilation, we suggest considering the use of MARS elimination therapy together with the monitoring of the BDZ plasma level.